A rare case of ovarian thecoma in a postmenopausal woman - Kulkarni, Yashwant S. S.; Kakade, Aniket S.; Singh, Bhumija A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Thecomas are very rare solid tumors of ovary and are a type of sex-cord stromal tumors. They account for approximately 0.5%-1% of primary ovarian tumors. We report a rare incidence of this tumor which presented in a postmenopausal woman. She presented with abdominal discomfort and underwent an ultrasonography revealing a solid ovarian tumor. She underwent a total abdominal hysterectomy with bilateral salpingo-oophorectomy. Histopathological examination showed benign thecoma. Hence it is important to keep this benign condition in mind when dealing with solid ovarian tumors in postmenopausal woman.